Chapter Capo Mele: a story-telling experimental beach in Laigueglia (sv) - Ghersi, Adriana (Proceedings e report, 2020)
The transformation of the coastal landscape assumes a significant importance, as far as global changes and erosion risks are concerned. The experience at Capo Mele to stage a new approach to the beach, managed by a smart private agent, allows more readings and new possible strategic actions. The initiative promotes the beach area as an active museum, to test and monitor new mechanisms for the use, protection and narration of landscape values, in the various aspects of adaptability, socio-cultural development and enhancement of the potential of the beach as a treasure chest of biodiversity.